Papers on the Early Identification of Exceptional Children - Illinois State Office of the Superintendent of Public Instruction, Springfield; Illinois State Office of the Superintendent of Public Instruction, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Intended especially for primary grade teachers, the nine papers provide general information regarding the characteristics of various kinds of handicapped children to assist teachers with early identification, making referrals, and educational programing. Articles explain the purpose of special education; why early identification of the mentally retarded is important; the health implications for early elementary handicapped children; the effects of learning disabilities on primary grade children and how to identify them; the difficulty, importance, and ways of identifying the visually impaired; the consequences of hearing impairment on language development and intellectual achievement; and the teacher's role in speech correction. Identified in each case are the classical characteristics of children categorized as retarded health impaired, learning disabled, visually handicapped, and aurally handicapped. In addition, papers review the psychological aspects of a handicap and suggest how and where teachers can obtain help for a handicapped child. (KW)
Educational level discussed: Primary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classification; Handicapped Children; Identification; Primary Education; Teacher Role